Targeting Biofilm-Forming Serratia marcescens by Bacteriophages and Disrupting Biofilm and Exopolysaccharide Production - AL-Balawy , Zakia F. S.; Mattar, Ehab H.; Al-maaqar, Saleh M.; Aly, Magda M. (Journal of Contemporary Medical Sciences, 2025)
Objective This study aimed to isolate two phages from soil and wastewater to assess their effectiveness in reducing biofilm and EPS production and disrupting biofilms in antibiotic-resistant S. marcescens. Methods: Soil and wastewater samples were added to a broth medium to allow phage infection of the bacterial host and enhance phage isolation. Bacteriophage titers, stability at different pH values and temperature, and host spectrum were detected. The effect of the combination of phage and antibiotics on the target host was recorded. Also, the inhibition of biofilm and EPS formation by the presence of phages was studied. Results: Two phages were obtained from wastewater and soil. Plaque morphology analysis revealed distinct characteristics for each bacteriophage. Both sources yielded high titers of phages specific to S. marcescens, with the wastewater-derived phage (S.wph) showing a slightly higher titer (1.67×109 PFU/ml) compared to the soil-derived phage (S.So.ph). The stability and host range of S.wph and S.So.ph were studied. The potential of S.wph to target multiple bacterial species could be valuable in developing phage-based therapies against diverse bacterial infections. The recorded MICs were 105 and 106 PFU/ml for S.wph and S.So.ph targeting S. marcescens, respectively. Ampicillin exhibited minimal inhibitory effects on S. marcescens with bacterial growth, while the combination of ampicillin with S.wph maintained the strongest antibacterial effect with no significant differences to S.wph monotherapy. In contrast, the ampicillin and S.So.ph combination displayed a moderate bacterial inhibition compared to ampicillin with S.wph, but there is a considerable difference compared to S.So.ph alone. Wastewater-derived phage (S.wph), soil-derived phage (S.So.ph), and their mixture inhibited biofilm formation and EPS secretion by S. marcescens. Conclusion: This research underscores the promising potential of bacteriophages as alternative treatments to conventional antibiotics, particularly in the face of increasing bacterial antibiotic resistance.